Exploring Teacher’s Perceptions as a Basis for Developing Deep Learning–Based Digital Assessment in Chemistry - Fershi Adi Saputra; Nahadi Nahadi; Wawan Wahyu (Journal of Educational Sciences, 2026)
The main challenge in 21st-century chemistry learning lies in the limited availability of assessment instruments that effectively measure students’ critical thinking skills in accordance with deep learning principles, namely meaningful, mindful, and joyful learning. In practice, teachers still predominantly employ conventional assessment methods that do not fully support technology-based learning or the development of higher-order thinking skills. As a preliminary study to support the development of deep learning–based digital assessment, this research aims to explore teachers’ perceptions and needs regarding the implementation of digital assessment in chemistry learning. A descriptive qualitative approach was employed, involving three senior high school chemistry teachers selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that teachers possess a sound pedagogical understanding of deep learning concepts; however, current assessment practices have not yet adequately captured the dimensions of meaningful, mindful, and joyful learning. Teachers expressed positive perceptions toward digital assessment as a means to enhance effectiveness and student engagement, despite challenges related to technological infrastructure and digital literacy. These findings provide an empirical basis for developing deep learning–based digital assessment instruments to strengthen students’ critical thinking skills and improve the quality of chemistry learning.